The social model in the international Convention on the Rights of Persons with Discabilities - Palacios, Agustina (2015)
Any analysis to be performed regarding disabilities requires a philosophical, sociological and regulatory framework. This paper takes as a starting point a philosophical framework which arises from those values and principles on which human rights are grounded. The sociological framework is built through the social model of disability, and the regulatory framework is provided by the InternationalConvention on the Rights of Persons with Disabilities.